2012
DOI: 10.1088/0031-9155/57/22/7673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhomogeneity in a patient's body on the accuracy of the pencil beam algorithm in comparison to Monte Carlo

Abstract: The pencil beam algorithm (PBA) is reasonably accurate and fast. It is, therefore, the primary method used in routine clinical treatment planning for proton radiotherapy; still, it needs to be validated for use in highly inhomogeneous regions. In our investigation of the effect of patient inhomogeneity, PBA was compared with Monte Carlo (MC). A software framework was developed for the MC simulation of radiotherapy based on Geant4. Anatomical sites selected for the comparison were the head/neck, liver, lung and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…The shortcoming of PB algorithms to accurately predict dose in low density media has been described previously 27 , 32 , 45 , 46 , 47 , 48 , 49 . In a recent study of 304 irradiations performed at 221 different institutions, Kry et al (49) observed an overestimate of 4.9% in PB algorithms compared to measurement in the Radiological Physics Center (RPC) thorax phantom used for RTOG credentialing; these results agree favorably with those reported here.…”
Section: Discussionsupporting
confidence: 86%
“…The shortcoming of PB algorithms to accurately predict dose in low density media has been described previously 27 , 32 , 45 , 46 , 47 , 48 , 49 . In a recent study of 304 irradiations performed at 221 different institutions, Kry et al (49) observed an overestimate of 4.9% in PB algorithms compared to measurement in the Radiological Physics Center (RPC) thorax phantom used for RTOG credentialing; these results agree favorably with those reported here.…”
Section: Discussionsupporting
confidence: 86%
“…Using Monte Carlo (MC) simulations in phantom geometries, Sawakuchi et al (Sawakuchi et al 2008) analyzed range degradation effects as a function of proton energy and geometric complexity. Range degradation can lead to an underestimation of the doses to critical structures distal to the target particularly in low-density regions (Yamashita et al 2012). In a review on range uncertainties, Paganetti estimated the uncertainties due to dose calculations alone to be between 2.7% (for homogeneous patient geometries such as liver fields) and 4.6% (for heterogeneous patient geometries such as head & neck fields) of the proton range when using standard analytical dose calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, most parameters evaluated still passed the initial acceptance criteria, although both sets of TLD results were approximately 4% lower than the TPS predicted dose. Previous studies have found an overestimation of the predicted dose by analytical dose calculations (compared with Monte Carlo calculations) [12], particularly near heterogeneities [13,14]. The coronal plane gamma analysis did not meet the proposed criteria, and the sagittal plane gamma analysis, along with the DTA in the anterior-posterior profiles, were only marginally within the proposed passing criteria.…”
Section: Discussionmentioning
confidence: 77%